Sustainable Bioplastics from Sweet Corn Cob Waste: Influence of Zinc Oxide and Glycerol on Mechanical Properties and Biodegradability - Nurhayati , Indah; Kurniawati , Cici Tri; Kholif, Muhammad Al (Indonesian Journal of Environmental Management and Sustainability, 2025)
The increasing environmental concerns associated with synthetic plastics have driven the search for biodegradable alternatives. This study investigates using sweet corn cob waste (Zea mays L. saccharata) for bioplastic production with varying concentrations of zinc oxide (ZnO) and glycerol as additives. The objective is to evaluate the influence of these additives on the mechanical properties, functional group composition, and biodegradability of the resulting bioplastics. The experimental procedures involved the delignification of corn cobs, bioplastic synthesis, and subsequent characterization through Fourier Transform Infrared Spectroscopy (FTIR), tensile strength and elongation tests, and biodegradability assessments. The results showed that increasing ZnO concentrations improved tensile strength, with the highest recorded at 9% ZnO and 25% glycerol. However, increased ZnO reduced elongation and biodegradability due to increased material stiffness. Conversely, higher glycerol concentrations enhanced flexibility and biodegradability but decreased tensile strength. The optimal formulation was identified at 3% ZnO and 35% glycerol, which provided a balanced combination of mechanical strength and biodegradability. This study demonstrates the potential of sweet corn cob waste as a sustainable raw material for bioplastics, contributing to environmentally friendly alternatives to conventional plastics.